2019
DOI: 10.4103/jomfp.jomfp_144_18
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and variability of five non metric dental crown traits in the permanent maxillary dentitions of a racially mixed population from Bengaluru, Karnataka

Abstract: Forensic CornerIntroduction: Evaluation of Tooth Crown non metric traits benefits to assess the biological distance between populations. It is well known that these traits are characterised by a high inter-population differentiation, low sexual dimorphism, and their recording is loaded by relatively small intra and inter observer error. The dental morphological traits are successfully used in the description and explanation of the microevolutionary and ethnogenetic processes. This paper presents the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…"Indodont" a.k.a. South Asian dental pattern has been followed by Sri Lankan aboriginal Vedda population with the exception that SH-UI1 which was not seen in the Vedda (Peiris et al 2011) Although it is well known that most of NDCTs which are part of ASUDAS have low or no sexual dimorphism (Scott et al 2018b;Venkatesh et al 2019). Contradicting to this, a Brazilian study has found frequencies of CC, 3-cusp UM2, and C6 to be sexually dimorphic (Tinoco et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…"Indodont" a.k.a. South Asian dental pattern has been followed by Sri Lankan aboriginal Vedda population with the exception that SH-UI1 which was not seen in the Vedda (Peiris et al 2011) Although it is well known that most of NDCTs which are part of ASUDAS have low or no sexual dimorphism (Scott et al 2018b;Venkatesh et al 2019). Contradicting to this, a Brazilian study has found frequencies of CC, 3-cusp UM2, and C6 to be sexually dimorphic (Tinoco et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Various researchers globally have ethnographically classified human populations based on dental morphology (Díaz et al 2014;Venkatesh et al 2019). Tsunehiko Hanihara defined the "Mongoloid dental complex" (Hanihara 1992), which was later divided into the Sinodont (Northeast Asian populations) and Sundadont (Southeast Asian populations) dental complexes by Turner (1984).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the dental morphological features of the three major races have merged, some traits are dominant in some ethnic groups [ 29 ]. Due to the wide range of morphological traits and their forms, human dental traits are helpful diagnostic tools for anthropological studies to identify and describe different ethnic groups [ 30 ]. The results of the present study helped establish the idea of regional or ethnic variation in dental morphometry by demonstrating variations in tooth dimensions among four ethnic groups from North-eastern India compared with the standard values.…”
Section: Discussionmentioning
confidence: 99%